Wireless ad hoc networks on underserved communities: an efficient solution for interactive digital TV - Campista, Miguel Elias M. (2006)
The Brazilian government intends to use the Digital TV technology as a vehicle of digital inclusion on underserved communities. The wireless ad hoc network is a low-cost, scalable and easy solution to implement the return channel. This work analyzes the performance of an ad hoc return channel using the wireless IEEE 802.11 technology in different Brazilian geographical scenarios. The results show that a high connectivity is achieved when more than 20% of the nodes are turned on, regardless of the position of the gateway. The influence of the number of hops and the number of transmitting nodes is also analyzed. A minimum throughput of 2 Mbps can be reached for increasing number of hops in the forwarding chain for a one-node transmission. Besides, when the number of transmitting nodes increases, the aggregated throughput can achieve 3.5 Mbps. The results show that the ad hoc network is a promising solution for the return channel of the interactive Digital TV.